The Children of 1965 : On Writing, and Not Writing, as an Asian American - Song, Min, 1970- (Book collections on Project MUSE., 2013)
A new generation of Asian American writers has garnered critical and popular attention since the 1990s. Min Hyoung Song argues that their diverse work pushes against existing ways of thinking about race.